PEMBERDAYAAN IBU-IBU DI DESA PASAURAN KECAMATAN CINANGKA PROVINSI BANTEN DALAM MENGISI KEGIATAN PKK MEMBUAT PRODUK KERAJINAN YANG BERDAYA JUAL - Dewi Suliyanthini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2015)
ABSTRACTCommunity Service (P2M) is one of the Tridharma Perguruan Tinggi which must be implemented by every lecturer. The implementation of devotion in the form of empowerment of PKK mothers in Pasauran village, Cinangka sub-district of Banten Province, is the activity of making handicraft products selling powerless. this handicraft product make mat mats from waste of coffee wrap, make bag of bag from waste coffee bingkus, and so forth. It is hoped that this activity can provide positive motivation and implication for the women of PKK and the young women in Pasauran village of Serang sub district of Cinangka, Banten Province